Prevalence of sexually transmitted infections and bacterial vaginosis among women in sub-Saharan Africa: An individual participant data meta-analysis of 18 HIV prevention studies. - Elizabeth A Torrone; Charles S Morrison; Pai-Lien Chen; Cynthia Kwok; Suzanna C Francis; Richard J Hayes; Katharine J Looker; Sheena McCormack; Nuala McGrath; Janneke H H M van de Wijgert; Deborah Watson-Jones; Nicola Low; et al. (PLoS Medicine)
Background Estimates of sexually transmitted infection (STI) prevalence are essential for efforts to prevent and control STIs. Few large STI prevalence studies exist, especially for low- and middle-income countries (LMICs). Our primary objective was to estimate the prevalence of chlamydia, gonorrhea, trichomoniasis, syphilis, herpes simplex virus type 2 (HSV-2), and bacterial vaginosis (BV) among women in sub-Saharan Africa by age, region, and population type. Methods and findings We analyzed individual-level data from 18 HIV prevention studies (cohort studies and randomized controlled trials; conducted during 1993-2011), representing >37,000 women, that tested participants for ≥1 selected STIs or BV at baseline. We used a 2-stage meta-analysis to combine data. After calculating the proportion of participants with each infection and standard error by study, we used a random-effects model to obtain a summary mean prevalence of each infection and 95% confidence interval (CI) across ages, regions, and population types. Despite substantial study heterogeneity for some STIs/populations, several patterns emerged. Across the three primary region/population groups (South Africa community-based, Southern/Eastern Africa community-based, and Eastern Africa higher-risk), prevalence was higher among 15-24-year-old than 25-49-year-old women for all STIs except HSV-2. In general, higher-risk populations had greater prevalence of gonorrhea and syphilis than clinic/community-based populations. For chlamydia, prevalence among 15-24-year-olds was 10.3% (95% CI: 7.4%, 14.1%; I2 = 75.7%) among women specifically recruited from higher-risk settings for HIV in Eastern Africa and was 15.1% (95% CI: 12.7%, 17.8%; I2 = 82.3%) in South African clinic/community-based populations. Among clinic/community-based populations, prevalence was generally greater in South Africa than in Southern/Eastern Africa for most STIs; for gonorrhea, prevalence among 15-24-year-olds was 4.6% (95% CI: 3.3%, 6.4%; I2 = 82.8%) in South Africa and was 1.7% (95% CI: 1.2%, 2.6%; I2 = 55.2%) in Southern/Eastern Africa. Across the three primary region/population groups, HSV-2 and BV prevalence was high among 25-49-year-olds (ranging from 70% to 83% and 33% to 44%, respectively). The main study limitation is that the data are not from random samples of the target populations. Conclusions Combining data from 18 HIV prevention studies, our findings highlight important features of STI/BV epidemiology among sub-Saharan African women. This methodology can be used where routine STI surveillance is limited and offers a new approach to obtaining critical information on STI and BV prevalence in LMICs.